تأثير المستخلصات الخلوية لبذور اليانسون في نمو الفطرين الممرضين Fusarium oxysporum و Aspergillus niger - علي, نوال; جنود, نجاة (Latakia University Journal -Biological Sciences Series, 2017)
درس في هذا البحث تأثير تراكيز مختلفة من مستخلصات بذور نبات اليانسون Pimpinella anisum L. الميتانولية والمائية بالإضافة للزيت في نمو الفطرين Fusarium oxysporum و Aspergillus niger ، وقد أظهرت جميع المستخلصات تأثيراً تثبيطياً واضحاً تجاه الفطرين الممرضين. تباينت الفعالية التثبيطية باختلاف التراكيز المستخدمة من المستخلص ونوع المذيب. عند استخدام المستخلص الميتانولي بالتراكيز (2، 4 و 6) ملغ/ مل بلغت النسبة التثبيطية في اليوم السابع 42.5، 50.6، 64.4 % للفطر F. oxysporum على التوالي. و 23.6، 42.7، و 55.1 % للفطر A. niger على التوالي. و بلغت النسبة التثبيطية لنمو الفطر F. oxysporum في اليوم السابع 59.2، 65.3 و 70 % على التوالي عند استخدام المستخلص المائي بالتراكيز السابقة، و وصلت إلى 46.1، 58، و 61 % عند الفطر A. niger. في حين سجل المستخلص الزيتي أعلى نسبة بلغت 100% عند 50 و 75 ميكرولتر للفطرين المدروسين.A Study was carried out to evaluate the ability of the methanolic, hydro and oily extractions of anise seeds (Pimpinella anisum L.) to inhibit the growth of the pathogenic fungi Fusarium oxysporum and Aspergillus niger. The results showed a good inhibition ability of the alcoholic and hydro extractions on the growth of the studied fungi. The inhibition ability differed due to the used concentrations. When the methanolic extraction was used by concentrations (2, 4, and 6) mlg/ ml at the seventh day, the inhibition ability was (42.5, 50.6 and 64.4)% of the fungus F. oxysporum, respectively. And was (23.6, 42.7 and 55.1)% of the fungus A. niger, respectively. Whereas when the hydro extraction was used by the same concentrations, the inhibition ability was (59.2, 65.3 and 70)% respectively for the fungus F. oxysporum, and (46.1, 58 and 61)% for the fungus A. niger, respectively. The oily extraction showed high inhibition ability, where the inhibition rate was 100% when the extraction was used by the two concentrations 50 and 75 μl for both two studied fungi.